2015
DOI: 10.1136/bcr-2015-211390
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in denture adhesive: a rare cause of copper deficiency in a patient on home parenteral nutrition

Abstract: A 65-year-old woman with Crohn's disease, who had been on home parenteral nutrition for many years, presented with perioral paraesthesia and a burning sensation in the mouth. Initial blood tests including serum ferritin, vitamin B12 and folate, were normal apart from mild pancytopaenia. Serum copper was low, in spite of receiving regular copper in her parenteral feeds. The copper in her parenteral feeds was increased initially, but when it did not improve, she was started on weekly intravenous copper infusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…High-iron feeding of rapidly growing rats thus causes CDA. Precedence for such mineral interactions has been established, as, for example, high zinc intake induces severe copper deficiency in humans [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-iron feeding of rapidly growing rats thus causes CDA. Precedence for such mineral interactions has been established, as, for example, high zinc intake induces severe copper deficiency in humans [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sutton et al [361] showed that cytopenia in patients can be caused by a high Zn concentration in the body combined with Cu deficiency, and Cu supplementation leads to a reversal of hematologic levels. According to Prasad et al [362], increased Zn concentration may be caused by improperly fitting dentures, resulting in increased use of dental adhesive, which contains high levels of Zn. Excess Cu can lead to both anemia and neutropenia as a result of the mechanisms in which Cu participates.…”
Section: Cu Vs Znmentioning
confidence: 99%
“…For patients treated with PN, the source of excess Zn may not necessarily be parenteral. For example, excessive intake of Zn from a denture adhesive was recently reported to cause ZICD for a patient on long‐term PN containing standard Cu provision 39 . The patient presented with mild pancytopenia and perioral paraesthesia, which did not respond to additional Cu provision but resolved after the adhesive was switched to a Zn‐free product.…”
Section: Cu Deficiencymentioning
confidence: 99%